Assessment of the kidney tumor vascular supply by two-phase MDCT-angiography - Ferda, Jirí; Hora, Milan; Hes, Ondrej; Ferdová, Eva; Kreuzberg, Boris (European journal of radiology, 2007)
PURPOSE: Current kidney surgery uses less invasive laparoscopic and nephron-sparring procedures. Thus, perfect imaging of the renal vasculature is essential for surgery planning. The aim of our retrospective study was to evaluate the accuracy of 16-detector-row CT-angiography in assessing the vascular anatomy of the kidney with a tumor. SUBJECTS AND METHODS: Referred for computed tomography (CT) because of a suspected renal tumor, 50 consecutive patients (mean age 58.6 years; range 43-82) were enrolled into our retrospective study. All examinations were performed with 16x0.75 mm collimation after the intravenous application of 80 ml of a non-ionic contrast material. The imaging protocol contained two-phase scanning in the arterial and then in the venous phase. The vascular anatomy of the kidney with tumor was evaluated using volume rendered (VRT) and maximum intensity images (MIP). Findings were compared with the anatomy found during surgery. RESULTS: Forty-seven patients underwent nephrectomy, with an advanced clinical stage (IV) found in the three remaining ones. Correct topography of the renal hilus, including a number of arteries and veins, and the anatomy of their branching, was described in 46 patients. A very small upper polar artery was overlooked in one patient. The accuracy for the only-arterial was 97.9% and only-venous anatomy was 100%. The parasitic vasculature of the tumor was discovered in 10 cases and all of them were confirmed by surgery (100% accuracy). Macroscopic intravenous spread of the tumor was discovered in two cases, but microscopic intravenous invasion was confirmed during histology of the kidney specimens in another two cases, the overall tumor staging accuracy reaching 95.7%. CONCLUSION: Two-phase multidetector CT is a valuable tool for assessing vascular supply of the kidney before surgery due to the tumor and can fully replace catheter-based angiography.
Keywords: nádory ledvin; venae renales; počítačová rentgenová tomografie; kontrastní látky; Renal Veins; Humans; lidé středního věku; Contrast Media; Female; Aged; Renal Artery; dospělí; Neoplasm Invasiveness; senioři; lidé; arteria renalis; počítačové zpracování obrazu; Image Processing, Computer-Assisted; Adult; staging nádorů; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Tomography, X-Ray Computed; Aged, 80 and over; karcinom z renálních buněk; senioři nad 80 let; Carcinoma, Renal Cell; invazivní růst nádoru; retrospektivní studie; Neoplasm Staging; Nephrectomy; mužské pohlaví; nefrektomie; prospektivní studie; Kidney Neoplasms; Prospective Studies